Holographic and Light Field Displays: What are the differences? - Son, Jung-Young; Lee, Hyoung; Park, Min-Chul; Lee, Beom-Ryeol; Byeon, Jina (2017 16TH WORKSHOP ON INFORMATION OPTICS (WIO), 2017)
Holographic and light field displays are currently themost researched 3-D imaging technologies. It is considered that the two imaging provide continuous parallaxes so that they can create a natural viewing environment. The main difference of the two imaging lies in their light fields in front of the display panel. The light fields in holographic displays are formed by phase conjugated rays from each hologram point and the light field display by an ever expanding fan beam from each pixel.